2006
DOI: 10.1159/000091437
|View full text |Cite
|
Sign up to set email alerts
|

No Genetic Association between the Myeloperoxidase Gene –463 Polymorphism and Estrogen Receptor-α Gene Polymorphisms and Japanese Sporadic Alzheimer’s Disease

Abstract: Myeloperoxidase (MPO) presence has been demonstrated in microglia associated with senile plaques and contributes to Alzheimer’s disease (AD) pathology through oxidation-induced damage. MPO activity is normally higher in women than in men. Additionally, a functional biallelic (G/A) polymorphism in the promoter region (–463) of the MPO gene has been associated with a gender-specific risk factor for AD, but reports of this association have been inconsistent. Furthermore, estrogen is known to enhance MPO activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…However, the frequency of the GG genotype in the HN group turned out to be virtually the same as that in the healthy controls ( Table 2). The frequency of the GG genotype in healthy controls in this study was approximately consistent with previous reports from Japan (15)(16)(17). The GG genotype was less frequent in the non-HN groups than in healthy controls (p= 0.0033).…”
Section: Distribution Of the -463g/a Polymorphism In Dialysis Patientsupporting
confidence: 92%
“…However, the frequency of the GG genotype in the HN group turned out to be virtually the same as that in the healthy controls ( Table 2). The frequency of the GG genotype in healthy controls in this study was approximately consistent with previous reports from Japan (15)(16)(17). The GG genotype was less frequent in the non-HN groups than in healthy controls (p= 0.0033).…”
Section: Distribution Of the -463g/a Polymorphism In Dialysis Patientsupporting
confidence: 92%
“…We identified 135 studies by electronic and manual search, of which 16 studies were selected for a full-text review on the basis of the title and abstract details (Isoe-Wada et al, ©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 14 (3): 9361-9369 (2015) 1999; Ji et al, 2000;Maruyama et al, 2000;Lambert et al, 2001;Lin et al, 2003;den Heijer et al, 2004;Pirskanen et al, 2005;Monastero et al, 2006;Porrello et al, 2006;Usui et al, 2006;Boccardi et al, 2008;Dresner-Pollak et al, 2009;Ma et al, 2009;Goumidi et al, 2011;Boada et al, 2012b;Deng et al, 2013). After full-text review, seven studies were excluded, of which 4 did not contain genotype data for ESR1 polymorphism (den Heijer et al, 2004;Pirskanen et al, 2005;Boccardi et al, 2008;Goumidi et al, 2011), 2 contained data on control genotype deviated from HWE (Maruyama et al, 2000;Boada et al, 2012b) and 1 study contained duplicate data (Isoe-Wada et al, 1999).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…After full-text review, seven studies were excluded, of which 4 did not contain genotype data for ESR1 polymorphism (den Heijer et al, 2004;Pirskanen et al, 2005;Boccardi et al, 2008;Goumidi et al, 2011), 2 contained data on control genotype deviated from HWE (Maruyama et al, 2000;Boada et al, 2012b) and 1 study contained duplicate data (Isoe-Wada et al, 1999). Thus, a total of 9 studies (Ji et al, 2000;Lambert et al, 2001;Lin et al, 2003;Monastero et al, 2006;Porrello et al, 2006;Usui et al, 2006;Dresner-Pollak et al, 2009;Ma et al, 2009;Deng et al, 2013), corresponding to 1359 patients and 1387 controls, met all the inclusion criteria and were considered for the ESR1 XbaI polymorphism meta-analysis (Table 1C). Of these, 8 studies corresponding to 1525 patients and 1575 controls were also included in the ESR1 PvuII polymorphism meta-analysis (Table 1B).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As well, several studies have already found an association between the A allele and increased risk of developing AD 16,17,18 . Usui et al 19 found a marginal association between the A allele of XbaI and an increased risk for AD in elderly Japanese men and women. Similarly, male Italian old individuals with XbaI AA genotype showed an increased risk for AD 20 .…”
Section: Discussionmentioning
confidence: 99%